Development of STEAM-Based Assessment Instrument for Creative Thinking on Static Fluid Material - Rasmi, Dian Pertiwi; Hendri, Menza; Mardatila, Akrom (Jurnal Pijar Mipa, 2025)
21st-century learning emphasises the importance of creative thinking skills through the STEAM approach, including developing STEAM-based learning models and tools. This study aims to develop a STEAM-integrated assessment instrument to measure students' creative thinking skills, as well as to determine students’ perceptions of the assessment instrument. The research and development (R&D) method produces effective and efficient educational products through improvement, development, and evaluation. The research was conducted at SMAN 1 Jambi City and SMA Adhyaksa 1 Jambi City, involving 40 students in class XI. The instrument was developed in the form of description questions on static fluid material. The results showed that students' perception was very positive, with an average assessment of 83.15% for the category ‘Very Feasible’. Validation consists of 3 aspects, namely material, language, and evaluation aspects, which show most aspects of the instrument are in the ‘very feasible’ to ‘feasible’ category. Nine of the 11 questions tested were declared valid, while 2 needed revision. The difficulty level of the questions varied from ‘moderate’ to ‘difficult’. These findings indicate that the instrument developed is feasible for measuring students' creative thinking skills in static fluid material with the STEAM approach. The novelty of this research lies in integrating STEAM components into assessment instruments that assess concept understanding and encourage the development of students' creativity.